KOMUNIKASI PUBLIK CALON GUBERNUR PROVINSI JAWA BARAT 2018 DALAM MEMBANGUN PERSONAL BRANDING MENGGUNAKAN TWITTER - Srisadono, Wahyu (Universitas Prof. Dr. Moestopo (Beragama), 2018)
Along with the development of internet technology with social media as a supporter in it, making personal branding activity becomes very open. Perception will form when one sees part of personal branding activity on social media. Social Media Twitter has a very important role for the candidates of Governor of West Java, to be able to communicate with the public, in building communication with the community and help him do personal branding to improve the image and popularity in the public eye.On that basis, in this research will see how public speaking of West Java Governor candidate in developing personal branding through social media account twitter in accordance with the eight laws of personal branding and characteristic of strong personal branding.